2017
DOI: 10.1177/1460408617706387
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of paediatric spinal cord injury

Abstract: Background: Spinal cord injuries are relatively uncommon in children and evidence about long-term outcomes is limited. This study was performed to determine the frequency of common long-term complications in patients sustaining spinal injury in childhood (0-18 years) and who were followed up at a single dedicated spinal injuries centre in the UK. Method: A retrospective review of clinical records of all patients injured at or less than 18 years of age between 1971 and 1999. Complications studied were renal, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 34 publications
5
9
2
Order By: Relevance
“…Road traffic accident is the usually reported leading cause of pediatric traumatic SCI in developed countries, while fall was once deemed to be the leading cause in some of the less developed countries. 16,22,25,26,37 Road traffic accident is, however, the most common cause of traumatic SCI in this study similar to what is being widely reported in the literature. Even so, certain characteristics of this mechanism of injury (road trauma) differ in our study cohort from what was previously documented.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Road traffic accident is the usually reported leading cause of pediatric traumatic SCI in developed countries, while fall was once deemed to be the leading cause in some of the less developed countries. 16,22,25,26,37 Road traffic accident is, however, the most common cause of traumatic SCI in this study similar to what is being widely reported in the literature. Even so, certain characteristics of this mechanism of injury (road trauma) differ in our study cohort from what was previously documented.…”
Section: Discussionsupporting
confidence: 86%
“…22,25,26,37 However, the mean age of our patients is lower than previously indicated. 22,25,26,37 There are proportionately more patients (30.0%) below the age of 10 years in our study than was previously documented, 16,22 while another 4 of our patients (20.0%) were younger adolescents (aged 10-12 years) (Fig. 1).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations